2000
DOI: 10.1080/00224540009600485
|View full text |Cite
|
Sign up to set email alerts
|

Body Image: Gender, Ethnic, and Age Differences

Abstract: Using figure drawings (E. Fallon & P. Rozin, 1985), 120 male and female U.S. college students--African American, Hispanic, and Caucasian--indicated their current and ideal figures, the figures that they considered most attractive to the opposite sex, and the opposite-sex figures most attractive to themselves. Dissatisfaction with body shape was greater among the women regardless of ethnicity. Both the men and the women misjudged which shapes the opposite sex would rate as most attractive: The women guessed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
150
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(181 citation statements)
references
References 14 publications
23
150
2
6
Order By: Relevance
“…In agreement with findings from several ethnic groups (42)(43)(44) , women in Immigrant-HUBRO were more prone to be dissatisfied with their bodies than men, and while women wanted to lose weight, men more often wanted to gain weight. About one out of three normal-weight women were dissatisfied with their weight.…”
Section: Weight Dissatisfaction and Slimming Attemptssupporting
confidence: 88%
“…In agreement with findings from several ethnic groups (42)(43)(44) , women in Immigrant-HUBRO were more prone to be dissatisfied with their bodies than men, and while women wanted to lose weight, men more often wanted to gain weight. About one out of three normal-weight women were dissatisfied with their weight.…”
Section: Weight Dissatisfaction and Slimming Attemptssupporting
confidence: 88%
“…Adolescent females wanted to be at least one half size smaller than their current size and reported greater body dissatisfaction and body size discrepancy than did males (Demarest & Allen, 2000;Gardner et al 1999). Caucasian females reported the highest BD scores and Caucasian males reported the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences; Ethnic differences; Body Image; Rural; Adolescents Numerous studies have shown that adolescent females are dissatisfied with their shape and weight and prefer a thinner body figure (Demarest & Allen, 2000;Gardner, Friedman, & Jackson, 1999). Males, by contrast, appear to be generally satisfied with their overall body shape and size, although some may wish to be larger or more muscular (Peixoto-Labre, 2002;Stanford & McCabe, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Other industrialized countries, including Taiwan, are beginning to experience an epidemic of excess body weight as peoples' lifestyles and diet became more westernized. [3][4][5][6] According to the National Nutritional and Health Survey in Taiwan, the mean body mass index (BMI) was 22.1, 24.6, and 24.8 kg/m 2 for age groups [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], and 65 þ years in 1993-1996, representing increases of 1, 5 and 9%, respectively, since a 1986-1988 survey. 5 Evidence suggests that overweight and obesity are important determinants of chronic diseases (CDs), including diabetes mellitus, hypertension, dyslipidemia, coronary heart disease, cardiovascular disease, some cancers, gallbladder disease, osteoarthritis, sleep apnea, and respiratory problems.…”
Section: Introductionmentioning
confidence: 99%